An Automatic Scheduling System for Perishable Product’s Supply Chain - Isbat Uzzin Nadhori; Ahmad Syauqi Ahsan (Politeknik Negeri Semarang, 2016)
Perishable products are a kind of agricultural product that has a very short shelf-life, such as fruits and vegetables. To maintain the quality, as expected by consumers, it needs a system that could be utilized to manage production planning of those perishable products. By utilizing this system should also minimize human error hence reducing the loss. To increase the availability of fruits and vegetables for people who live in cities is by shortening the distance between supplier (farmer) and consumer (citizen). Urban Farming is one way to increase the availability of fruits and vegetables for people who live in city. To create an efective Urban Farming infrastructure, it need a system by utilizing information technology to manage its supply chain. All members of the supply chain network including producers (farmers), distribution center, administrator, retailers, and consumer can access this system. Members of the supply chains can manage every information related to him/her, and able to see the information of the other members when needed. With the integrated information, the planting schedule planning process, the selection of products that will be planted, harvest schedules, and reports related to the fulfillment of the request can be done easily and faster